Persistent left superior vena cava. A case report - Rondón-Tapia, Marta (2018)
Persistent left superior vena cava is the most frequent congenital venous anomaly, observed in 0.3-0.5% of the general population and in 4-8% of patients with congenital heart disease. The perinatal outcome is significantly worse if it is associated with cardiac defects and the prognosis is excellent in isolated cases. We report a case of persistent left superior vena cava diagnosed in a 30-week fetus in a 21-year-old female patient referred for prenatal fetal echocardiographic evaluation. During the visualization of the three vessels, a supernumerary circular vascular structure was observed to the left of the pulmonary artery, extending into the lateral wall of the left atrium, consistent with persistent left superior vena cava. No other heart abnormalities were found. The pregnancy was uncomplicated and a healthy baby was born full-term without any complications. Postnatal echocardiography confirmed the diagnosis. No intervention was necessary.